The interaction of receptor-type protein tyrosine phosphatases sigma and zeta1 controls cardiac fibroblast migration. (3rd October 2022) - Hasselbach, L; Weidner, J; Elsaesser, A; Theilmeier, G
Abstract: Background: Among cardiovascular diseases as a major health burden heart failure (HF) plays a central role. Our screening of patients with HF either from ischemic – or dilatative cardiomyopathy has shown that receptor-type protein tyrosine phosphatase sigma (PTPRσ) and zeta1 (PTPRz1) are upregulated compared to healthy hearts. Inhibition of PTPRσ is known to be necessary for autonomic reinnervation after myocardial infarction [1] and for various functions in the nervous system [2]. Most recently the loss of PTPRz1 in knockout-mice has been shown to lead to impaired morphogenesis with postnatal systolic and diastolic heart failure [3]. Purpose: A crucial step in myocardial remodeling and the development of HF is fibroblast migration into the wound, where they differentiate into myofibroblasts, producing extracellular matrix proteins and forming the scar. Up to now no information is available on the role of PTPRσ and PTPRz1 in fibroblast migration and myocardial remodeling. Methods: Neonatal cardiac fibroblasts are transfected with either scrambled-, PTPRσ-, PTPRz1-siRNA or a combination thereof. A scratch wound is inflicted at confluency of the cells. The number of migrated cells, relative to the control, is determined microscopically after 48 hours. Transfected fibroblasts are seeded into transwells to examine their transmigration. After 48 hours the number of transmigrated cells, relative to the control, is determined after DAPI staining. N=4, statistical analysis is performed using Kruskal-Wallis Test with Dunn's multiple comparison. Results: In the scratch assay a PTPRz1 knockdown resulted in a significant increase in migrating cells (1 vs. 1, 355±0, 1144, p=0, 0265). This promigratory effect is not present in PTPRσ knockdown cells, independent of the PTPRz1 expression (1 vs. 1, 032±0, 1654 and 1 vs. 1, 073±0, 08597, both p>0, 9999). In transmigration there is a fourfold increase in transmigrated cells after PTPRz1 knockdown (1 vs 4, 046±0, 4865, p=0, 05). Like in migration this effect is reversed after downregulation of PTPRσ (1 vs 0, 9834±0, 3844 and 1 vs. 1, 345±0, 6584, both p>0, 9999). Conclusion: PTPRσ and PTPRz1 are differentially regulated during the pathogenesis of heart failure. While a knockdown of PTPRz1 leads to an increase in fibroblast migration and transmigration, downregulation of PTPRσ inhibits this effect. These results indicate an antimigratory role for PTPRz1. We hypothesize that PTPRσ and PTPRz1 interact through shared intracellular effector molecules, affecting fibroblast migration, an important step in myocardial remodeling and the development of HF. Further investigations will be conducted to identify these shared effector molecules of PTPRσ and PTPRz1 to find a way to influence heart failure through regulation of receptor-type protein tyrosine phosphatases. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Carl von Ossietzky University Oldenburg